Do mate preferences influence actual mating decisions? Evidence from computer simulations and three studies of mated couples. [article]. - Conroy-Beam, Daniel
Evolutionary research continues to discover new features of human mate preferences, but the downstream consequences of these preferences for mate selection have been insufficiently explored. Some have inferred that stated preferences have few behavioral consequences given seemingly weak effects of preferences in predicting mating outcomes. Here we test this inference with data from simulated mating markets as well as from real-world couples. We generate a series of agent-based models in which preferences either do or do not drive mate selection. We compare these simulations with 3 empirical studies of real-world couples (Study 1, n = 214; Study 2, n = 259; Study 3, n = 294). Preference-driven agent based models produce several effects that emerge in real couples, but not within random simulations. These include low-magnitude correlations between stated preferences and the individual traits of chosen partners; the novel finding that people with high mate value leverage that value into securing partners with more desirable traits; and the finding that couples assort based on overall mate value. Moreover, real-world mate choices correspond strongly with preference-driven simulations, but not to simulations in which mate selection is random with respect to preferences. Finally, we provide evidence that these effects are due to the causal role of stated preferences, and are not better explained by people updating their mate preferences to match chosen mates. These results provide new evidence that stated mate preferences guide actual mate selections under real mating-market constraints. -- (from the authors)
Keywords: Buss, David M; Mate preferences; Mate selection; Mate value; Agent-based models; Evolutionary psychology